2021
DOI: 10.1108/techs-09-2021-0005
|View full text |Cite
|
Sign up to set email alerts
|

Technology aspect of Electric Vehicles Initiative's social sustainability

Abstract: PurposeThe Electric Vehicles Initiative (EVI) is a multi-government policy forum devoted to speed up the introduction and adoption of electric vehicles (EVs) worldwide. EVI key themes for sustainable development include energy-efficient transportation with e-mobility (drive-by science and technology), reduced greenhouse gas emissions, decreased oil dependence and improved local air quality. India's transport sector contributes around 142 million tons of CO2 every year, with road transport contributing 123 mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Thus, it is clear that the use of EVs offers more benefits than fuel-based vehicles and business organizations can reap its benefits for their efficient performance (Pernestål et al. , 2020; Tyagi and Vishwakarma, 2022; Dias, 2022, [8]).…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, it is clear that the use of EVs offers more benefits than fuel-based vehicles and business organizations can reap its benefits for their efficient performance (Pernestål et al. , 2020; Tyagi and Vishwakarma, 2022; Dias, 2022, [8]).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Finally, the study found that the adoption of EVs in the business process offers many benefits to business organizations such as minimized operational costs, eco-friendly business model, more tax incentives, less BPCs, low-emission footprint and contribution towards SD at large (Pernestål et al. , 2020; Tyagi and Vishwakarma, 2022). These results of the study add to the rapidly expanding field of research on the current topic and it also serves as one of the foundational research on EV-based business models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations